The association between serum estradiol level and stress score with sexual function in women admitted to Shohadaye Yaftabad Hospital (Simultaneously with the outbreak of coronavirus) - Elahe Sadeghi Sahebzad; Najmeh Tehranian; Anooshiravan Kazemnezhad; Mohsen Sharifi; Faraz Mojab (Mashhad University of Medical Sciences, 2022)
Introduction: Sexual function is a part of human life and behavior and is a multidimensional phenomenon that is influenced by a variety of biological, psychological, and social factors. Estradiol is the hormone which is directly related to the level of sexual function. Prevalence of Covid 19 virus causes severe mental and physical stress which may result in reduced sexual function. This study was performed aimed to determine the association between serum estradiol levels and stress score with sexual function in women referred to Shohadaye Yaftabad Hospital (simultaneously with the outbreak of coronavirus). Methods: This correlational study was performed in 2021 on 223 pregnant women aged 18-35 years referred to the gynecology clinic of Shohadaye Yaftabad Hospital (simultaneously with the outbreak of coronavirus). The women underwent venous blood sampling in the follicular phase and then completed the demographic characteristics (including personal information), the Sexual Function Index (FSFI), and the DOS Stress Questionnaire. Data were analyzed using SPSS software (version 21) and Pearson correlation test and one-way analysis of variance. P<0.05 was considered statistically significant. Results: According to the Pearson correlation test, the mean of the total score of sexual function had a significant inverse correlation with stress (p <0.001, r =0.983). In other words, the more stress reduced the score of sexual function. Also, based on this test, estradiol levels have a positive correlation with sexual function (p =0.001, r = -0.223). Conclusion: According to this research, the stressful conditions including the coronavirus pandemic resulted in reduction of sexual function and estradiol levels.